IDENTITY DEVELOPMENT OF IMMIGRANT CHILDREN AS PORTRAYED IN MY NAME IS YOON AND YOON AND THE CHRISTMAS MITTEN - Kristin Marwinda (Universitas 17 Agustus 1945 Semarang, 2020)
The topic of cultural differences in picture books can be used as a medium for school-age children to understand more about the condition of immigrant children in America. “Through picture books about immigrants, nonimmigrant children can learn about the immigrant experience (Johnson and Smith, 1993) and be exposed to different cultures in the social studies classroom” (Lamme, Linda, et al., 2004: 123). This issue becomes very interesting to be analyzed because the readers will get more understanding on how immigrant children face several cultural differences in America, especially on how they develop their identity. The purpose of this study is to analyze the identity development of immigrant children in America as portrayed in Yoon character in the picture books by Helen Recorvits. As a Korean girl who moves to America, Yoon has to adapt and adjust with new different environment. The method of this study is descriptive qualitative based on the library research. This paper uses sociological approach to analyze the story of Yoon in the picture books. The result of this study shows that Yoon has experienced adjustment and acculturation during her adaptation to American culture. She has gradually undergone a change of identity, which is from a Korean girl to be an Asian-American. Keywords: picture books, immigrant children, adjustment, identity development